Pandangan Pasangan Muslim terhadap Program Keluarga Berencana (KB) di Puskesmas: Studi Kualitatif - Khuzaimah Adinda; Is Susiloningtyas; Machfudloh Machfudloh (Faletehan Health Journal, 2023)
Family planning is a program to help married couples avoid unwanted births, regulate desired pregnancies, and manage the distance of children births. One of the obstacles of family planning program is different view of spouse, especially Moslem couples. The research purpose was to know Moslem couples views on family planning program in public health center. The informants of this study amounted to 2 midwives and 5 Moslem couples who were selected by using purposive sampling technique. The data collection used in-depth interview technique. This study resulted three main themes, including: 1) knowledge of Moslem couples about family planning program, 2) basis of Moslem couples using family planning programs, and 3) family support to family planning program. The researcher concluded that most of informants in this study already knew about family planning program and agreed about the use of contraceptives for Muslim couples.